New Amino‐Acid‐Based β‐Phosphorylated Nitroxides for Probing Acidic pH in Biological Systems by EPR Spectroscopy. (16th December 2016) - Thétiot‐Laurent, Sophie; Gosset, Gaëlle; Clément, Jean‐Louis; Cassien, Mathieu; Mercier, Anne; Siri, Didier; Gaudel‐Siri, Anouk; Rockenbauer, Antal; Culcasi, Marcel; Pietri, Sylvia
Abstract: There is increasing interest in measuring pH in biological samples by using nitroxides with pH‐dependent electron paramagnetic resonance (EPR) spectra. Aiming to improve the spectral sensitivity (ΔaX ) of these probes (i.e., the difference between the EPR hyperfine splitting (hfs) in their protonated and unprotonated forms), we characterized a series of novel linear α‐carboxy, α′‐diethoxyphosphoryl nitroxides constructed on an amino acid core and featuring an (α or α′)‐C−H bond. In buffer, the three main hfs (aN, aH, and aP ) of their EPR spectra vary reversibly with pH and, from aP or aH titration curves, a two‐ to fourfold increase in sensitivity was achieved compared to reference imidazoline or imidazolidine nitroxides. The crystallized carboxylate10 b (p K a ≈3.6), which demonstrated low cytotoxicity and good resistance to bioreduction, was applied to probe stomach acidity in rats. The results pave the way to a novel generation of highly sensitive EPR pH markers. Abstract : McConnell's equation helps EPR pH probing . β‐Phosphorylated nitroxides with a β′‐amino acid core provide enhanced pH sensing in the acidic pH region. To illustrate this, a stable, biocompatible, crystallized model carboxylate resistant to bioreduction was applied to assess rat stomach acidity.